Controlling the active surfaces of the Velvet Fingers: sticky to slippy fingers - V. Tincani; G. Grioli; M. G. Catalano; M. Bonilla; M. Garabini; G Fantoni; A. Bicchi (IEEE/RSJ International Conference on Intelligent Robots and Systems, IROS 2013, 2013)
Industrial grippers are often used for grasping, while in-hand re-orientation and positioning are dealt with by other means. Contact surface engineering has been recently proposed as a possible mean to introduce dexterity in simple grippers, as in the Velvet Fingers smart gripper, a novel concept of end-effector combining simple under-actuated mechanics and high manipulation possibilities, thanks to conveyors which are built in the finger pads. This paper undergoes the modeling and control of the active conveyors of the Velvet Fingers gripper which are rendered able to emulate different levels of friction and to apply tangential thrusts to the contacted objects. Through the paper particular attention is dedicated to the mechanical implementation, sense drive and control electronics of the device. The capabilities of the prototype are showed in some grasping and manipulation experiments.
Keywords: Robotics

Contenitore per alimenti caldi e simili - M. Bonini; R. Casati; M. Falorni; G Fantoni; M. Massei; D. Mazzei; M. Mazzuoli; G. Renucci (2010)
Keywords: Bioengineering